(3cJGH aj GdNjds
(3ChdgG (B:s
(3Qhi Yf Ydi Hf CHj WGdH cQe Gddg hLgg Yf SjOfG QShd Gddg Udi Gdgd Ydjg hSde Cfg bGd deG GQGO Gddg JYGdi Cf jNdb GdaQS bGd ddQjM s
(3BNQgG (B:s
(3hCfgG eCNhPI ef GdcJH Yf SjOfG SdjeGf GHf OGhO YdjgeG GdSdGe hYdi fHjfG CaVd GdUdGI hGdSdGe hYdi SGFQ GdCfHjGA hGdeQSdjf hHg Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs